Addressing the quality of life needs of older patients with cancer: a SIOG consensus paper and practical guide. (13th July 2018) - Scotté, F; Bossi, P; Carola, E; Cudennec, T; Dielenseger, P; Gomes, F; Knox, S; Strasser, F
Abstract: Around 60% of people living with cancer are aged 65 years or older. Older cancer patients face a unique set of age-associated changes, comorbidities and circumstances that impact on their quality of life (QoL) in ways that are different from those affecting younger patients. A Task Force of the International Society of Geriatric Oncology recommends and encourages all healthcare professionals involved in cancer care to place greater focus on the QoL of older people living with cancer. This paper summarizes current thinking on the key issues of importance to addressing QoL needs of older cancer patients and makes a series of recommendations, together with practical guidance.